The Optimization of Mechanical Properties of HDPE-Pineapple Fiber Composites Using the Taguchi Method - Ojahan Rajagukguk, Tumpal; Anshori, Anang; Isnugroho, Kusno; Hendronursito, Yusup (Science & Technology Asia, 2024)
This research investigates the potential of High-Density Polyethylene (HDPE) waste as a polymer matrix and reinforcing filler from pineapple leaf fibers (PLFs). This experiment uses the Taguchi orthogonal array L9 design with parameters of fiber volume (5%, 10%, and 15%), fiber direction (0◦, 45◦, and random), and fiber length ratio (continuous, 1:2, and 1:3). Taguchi analysis is used to determine the optimization of parameters on the mechanical properties of the composite. In contrast, analysis of variance (ANOVA) is used to determine significant parameters. Tensile strength test according to ASTM D638-04 and three-point bending according to ASTM D790 02 are conducted. Based on Taguchi, the maximum tensile strength obtained from this composite is 1.48 N/mm2 from 5% fiber volume, while the flexural strength is 1.61 N/mm2 obtained from the 0◦ fiber direction. The S/N ratio shows the composite with 5% fiber, 0◦ orientation, and 1:3 fiber length ratio together provides the greatest tensile strength. For flexural strength, the best choice is a composite with 15%, 0◦ fiber direction, and 1:3 fiber length ratio. The fiber volume parameter has the most significant influence in producing a composite with high mechanical strength. The amount of fiber filler used is influenced by the direction of the load acting on the composite. The composites from this research are suitable for use on materials that receive low to medium loads and provide an alternative composite option.